Sleepiness and Fatigue among Night - Shift Nurses with Three - Hour Nap and Day - Shift Nurses - Saadat 1, Soheil; Sadeghian 1, Farideh; Fayaz 2*, Mahsa (Shahroud Journal of Medical Sciences, 2016)
Background: Deficiency of sleep among nurses working in shifts, results in sleepiness, fatigue, health, and safety problem, and it also can deteriorate the quality of care provision. The present study aimed to compare sleepiness and fatigue between night-shift nurses who have a 3-h nap and day-shift nurses.Methods: A prospective cohort study was done on 23 night-shift nurses with a 3-h nap and 24 day-shift nurses in Sina Hospital in Tehran (Iran) during 2015–2016. Subjective sleepiness and fatigue before and after their shifts were measured by Stanford Sleepiness Scale (SSS) and Swedish Occupational Fatigue Inventory (SOFI-20), respectively. Statistical analysis including independent t-test, Mann–Whitney test, multivariate analysis of variance, and discriminant analysis were performed to compare the two groups.Results: The difference in means of subjective sleepiness before and after the shifts was significantly greater among night-shift nurses having a 3-h nap (1.43±1.50) than the day-shift nurses (0.37±0.92) (P=0.007). Although after their working shifts, the night-shift nurses (1.40±2.30) were more fatigued than the day-shift ones (0.96±1.46), this was not statistically significant (P=0.81). Moreover, day or night shift working with a 3-h nap was an effective factor (P=0.015) while considering the interrelationship between sleepiness and fatigue in multivariate analysis. Discriminant analysis revealed the dominant role of subjective sleepiness in differentiating the two groups. Conclusions: Despite the 3-h nap, subjective sleepiness was seen more among the night-shift nurses than the day-shift ones; however, the mean difference scores of fatigue did not differ between the two groups. Presumably, getting a 3-h nap during night shift and a heavy work load for day-shift nurses might result in insignificant fatigue between the groups. Furthermore, studies with new strategies for napping among nurses are recommended.